Junior athletes’ emotional intelligence in the context of adaptability to changed conditions of learning and training activities - Burlakova, Iryna; Piletska , Liybomyra; Kornienko, Victoria; Oksiutovych , Maryna; Kondes, Tetiana; Okhromiy, Halyna; Donets, Olesia; Кондес, Тетяна Василівна; Кондес, Тетяна (Editura Universitatii din Pitesti, 2025)
The aim is to conduct theoretical and empirical research into statistical relationships and differences in the parameters of junior athletes’ emotional intelligence in changed conditions of learning and training activities. Methods. The research participants, aged 14 to 19, with a total number of n = 124 people, represented sports schools of the Olympic Reserve for children and youth. The sample included representatives of team and individual sports, participants and winners of sports competitions – from regional and local domestic tournaments of sports federations to European and World Championships. The research variables were measured using valid and reliable psychological instruments tested on junior sports samples. Results. Operationalizing the profile of the junior athlete’s change readiness, proposed in the study, in the learning and training process can have a significant effect and give a competitive advantage over competitors. Twenty-six significant correlations were established, three of them being inverse. It was found that emotional intelligence and personal change readiness are closely related phenomena. Adaptability was relevantly identified as a mediating variable since adaptability is the most dependent and loaded variable. There was a caveat that high values of the parameters of adventurousness, passion, and resourcefulness together can lead to fatal mistakes. It was established that respondents with high levels of adaptability (Group 1) have significant superiority in the parameters “emotion management” and “emotion recognition”. Discussion and conclusions. It was substantiated that the research into junior athletes’ emotional intelligence in the context of adaptability to changed conditions of learning and training activities is a successful attempt to clarify the role of the internal potential of junior athletes who are educated and trained at sports schools of the Olympic Reserve and achieve their professional development in crisis situations of sports activities. It was explained that changed conditions are characterized by emotional tension that reflects the competitive environment, which contributes to the relevance of training. At the same time, additional permanent obstacles do not allow athletes to develop the skills of special technical training safely and reliably. The established psychological correlations and the identified significant differences in the studied parameters possess scientific novelty and can be implemented in the learning and training process of sports educational institutions.
Keywords: adaptation; self-regulation; motivation; mental health; empathy; educational and professional activities; mental state; stress